Living French colonial theory : an examination of France's complex relationship with Islam in its African colonies as viewed through the lives of Octave Houdas and Xavier Coppolani - Masey, Rachael (Department of Historical Studies, 2015)
Includes bibliographical references (leaves 89-94).